Internationalisation of curriculum delivery: complexities of english as an instructional language in a non-english culture - Mohd Faiz, Nur Sofurah; Mohamed, Maziana (2022)
English language is the main lingua-franca in higher education worldwide. For that reason, higher education institutions in Malaysia including the Malaysian Technical and Vocational University (MTVU, a pseudonym) have been promoting English as the language of instruction. With the existence of international students and voluminous English academic resources, implementing English as the language of instruction is a significant commitment. International students, as well as academic staff in MTVU however, come from various non-western cultures where English is not their native language. This paper focuses on an issue related to the use of English language amongst these groups in learning and teaching processes. Jin’s (1992) theories underlying Cultural Synergy model was used as the underpinning theories of the study. Data collected were from focus group and semi–structured in-depth interviews which were conducted with eleven international students and nine academic staff in MTVU. Through interpretive thematic analysis, findings highlighted that limited English proficiency is not only an issue solely for international students, but also for academic staff. This paper reveals this unique and complex issue from the perspectives of both students and staff. The paper then further discusses the consequences of these complexities for the learning and teaching environment.